Beethoven sculpture by Thomas Crawford - Grozelier, Leopold, 1830-1865 (artist):::Creator::::::::::::; Crawford, Thomas, 1814-1857 (sculptor):::Contributor:::::::::::: (Boston, MA; Nathan Richardson Musical Exchange)
Original lithograph printed by S.W. Chandler & Bro., Boston. Image is likely a drawing (bust only) of sculptor Thomas Crawford's bronze statue of Beethoven that was unveiled on March 1, 1856 as part of the Beethoven Festival in Boston.